Bebas-Aktif: On the Law of Neutrality Applicable to Indonesia - Afriansyah, Arie; Nasu, Hitoshi (Indonesian Journal of International Law, 2025)
Tensions have heightened in the Indo-Pacific, with the People’s Republic of China engaging in aggressive behaviors in the South China Sea, confronting India in border disputes, and poising itself for a forcible unification of Taiwan in the midst of a great power competition with the United States. While the situation remains precarious, it is imperative for Indonesia to consider how it might position itself if a large-scale armed conflict erupted in the region. Indonesia could plausibly maintain a neutral status without taking part in hostilities, pursuant to its long-standing “free-active” foreign policy. In such a case, the law of neutrality will regulate Indonesia’s relationship with belligerent parties according to corresponding rights and obligations derived from neutral status. However, this body of law is in a state of constant flux, with pragmatic considerations often prevailing over normative consistency. This article explores how Indonesia might implement the law of neutrality to maintain peaceful relations with belligerent parties, with a focus on three specific issues pertaining to its national interest: (1) closure of its archipelagic waters; (2) arms export control; and (3) the protection of its cyber infrastructure. This article concludes by finding that Indonesia is well positioned to make a pragmatic choice based on the geopolitical and socioeconomic conditions prevailing at the time but must pre-empt various legal risks by building its practice and expressing its opinio juris to shape the development of customary international law in this field.